THE ROLE OF LAND REDISTRIBUTION CERTIFICATES FOR THE IMPROVEMENT OF COMMUNITY WELFARE IN WEST PASAMAN DISTRICT - Monsaputra Monsaputra; Khursatul Munibah; Dyah Retno Panuju (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
Land redistribution of landreform objects was a government program to reorganize the control, and ownership of land in a just manner. West Pasaman Regency is one of the regions that implements land redistribution and encourages the use of certificates as collateral to access capital. There were 871 land redistribution certificates used for collateral in 2009 - 2018 (7.79%). West Pasaman Regency is currently in the fourth position with the highest number of poor people in West Sumatra Province. This study aims to analyze the effect of capital utilization on public welfare. The methods of analysis used were quantitative with surveys and the data analysis technique used was a correlation. In general, the majority (75%) of utilization of land redistribution certificates to obtain loans were related to agricultural activities. The role of certificate collateralization in reducing poverty was indicated by the slight drop of poverty proportion from 12% before the use of land-certificate for obtaining loan to 7% afterwards. The relationship between expenditure before and expenditure after additional capital from land certificate appears significant.